Chemical composition of and quantification of PAHs in cachaças commercialized in pet bottles and in cachaças aged in oak (Quercus sp.) casks with different thermal treatments - Barbosa, Richard Bispo (2021)
In Brazil, cachaça is considered a cultural heritage, born with the country's history, gaining more and more space in the national and international market. The sector is undergoing changes in the marketing of its product, from new labels, derivatives and different types of beverage packaging, such as PET polymeric packaging. These have been used by some producers, due to their lower cost and greater durability for transport. The aging technique is used to add value to cachaça and other beverages; During the contact of the cachaça with the wood, reactions occur that are responsible for the extraction and formation of new compounds that give a different color and aroma to the drink. The influence of the storage of 15 samples of commercial cachaça stored in polymeric packaging was studied. In a second step, the influence of different levels of charring of oak barrels (no charring, weak charring, medium charring and intense charring) on cachaça aged in those barrels was determined. The physicochemical profile, the phenolic compounds and the concentration of Polycyclic Aromatic Hydrocarbons (PAHs) were analyzed. The results for 60% of the samples stored in PET containers were outside the Quality and Identity Standards (PIQs) established by the Ministry of Agriculture and Supply (MAPA), and most of the samples had low alcohol concentrations. All the samples studied contained concentrations of PAHs higher than those found in the literature for cachaça stored in other types of packaging. The physical-chemical profiles of the beverages stored in oak barrels were within the standards required by legislation, with the exception of the RY3 sample for the quantification of aldehydes, which was above the legal limit (30.41 mg 100 mL-1 a.a.). Among the samples aged in barrels with different levels of charring, the highest concentration of phenolic compounds (36.43 mg L-1) was found in the cachaça stored in the barrel with medium charring (RY3), and gallic acid was the principal compound found in all the samples. The highest concentrations of HPAs were found in samples stored in barrels with medium and intense charring, so the formation of these compounds appears to be associated with heat treatments.